Hubungan Tingkat Pengetahuan Dan Sikap Swamedikasi Obat Tanpa Resep Dokter Pada Mahasiswa Farmasi Stikes BCM Pangkalan Bun Tahun 2024 - Rahmawati, Linda (Universitas Pahlawan Tuanku Tambusai, 2024)
Introduction: According to The Central Statistics Agency, Central Kalimantan has a self-medication prevalence of 80.73% and is increasing every year. Self-medication among students is 63.4%, therefore this research aims to determine the level of knowledge and attitude of self-medication without a doctor's prescription among students. Objective: To determine the level of knowledge regarding the attitude of self-medication of pharmacy students, as well as the relationship between the attitude of self-medication of drugs without a doctor's prescription and the level of knowledge of students at Stikes BCM Pangkalan Bun. Method: Study non experimental quantitative descriptive cross-sectional with data collection techniques Purposive Sampling. The total sample was 75 students. Results: At the level of knowledge, the results showed that 59 pharmacy students (78.7%) had a good level of knowledge, 7 pharmacy students (9.3%) had a sufficient level of knowledge and 9 pharmacy students (12.0%) had a poor level of knowledge. Meanwhile, the self-medication attitude was found in 75 pharmacy students (100%) where the self-medication attitude had a good level of knowledge, and (0%) had sufficient knowledge & poor knowledge. Conclusion: The relationship between the level of knowledge and attitude towards self-medication without a doctor's prescription among pharmacy students was found to be significant (0.000 <0.05). Keywords: Level Of Knowledge, Self-Medication Attitude, Non-Prescription Medication